TEACHER'S EXPERIENCE IN TEACHING ENGLISH TOWARDS DEAF STUDENTS - Amin, Nusaindah Nurul; Damanik, Emeliya Sukma Dara; Rahman Hz, Benni Ichsanda (BRIGHT VISION Journal of Language and Education, 2024)
This study examines the experiences and strategies of a teacher specialized in English instruction for deaf students at special need school in Medan North Sumatera Indonesia. Since 2017 the teacher has navigated significant challenges, including communication barriers and emotional strain, by integrating sign language (SIBI and Bisindo) into daily interactions and instructional methods. Initial self-learning of sign language, followed by formal training from the North Sumatera Language Center, highlights the critical role of effective communication in enhancing educational outcomes for deaf students. The teacher’s adaptive strategies include simplifying lesson content, employing visual aids, and incorporating sign language into English instruction. Innovative methods such as “English day” in morning assemblies underscore the teacher’s commitment to engaging students despite their disabilities. However, obstacles persist, including limited vocabulary, the complexities of teaching a foreign language to students struggling with their narrative language, and systematic issues like lack of resources and societal skepticism. Emotional management and building trust with students are central to the teacher’s approach, demonstrating a holistic commitment to their emotional and academic development. The teacher’s resilience and empathy, supported by the school’s flexible approach, have fostered positive student engagement and progress.